Efficacy of low-dose [D.sub.2]/[D.sub.3] partial agonist pramipexole on neuroleptic-induced extrapyramidal symptoms and symptoms of schizophrenia: a stage-1 open-label pilot study - Weng, Jia Jun; Wang, Li Hua; Zhu, Hao; Xu, Wen Rong; Wei, Yu Mei; Wang, Zhi Yang; Yu, Wen Juan; Li, Hua Fang (Neuropsychiatric disease and treatment, 2019)
Objective: Some lines of evidence show that [D.sub.2]/[D.sub.3] receptor partial agonist pramipexole may be effective in the treatment of extrapyramidal symptoms (EPS) and psychiatric symptoms of schizophrenia. Therefore, we analyzed whether a low dose of pramipexole (0.375-0.75 mg/day) has efficacy on EPS and symptoms of schizophrenia while maintaining tolerability. Methods: Ten subjects with EPS [including drug-induced parkinsonism (DIP) and akathisia] were recruited in a stage-1, open-label pilot study. All the subjects were treated with a low dose of pramipexole. The evaluations were performed at baseline, day 3, week 1, week 2, week 4, week 6, and week 8. The ratings of SAS, BARS, PANSS, CDSS, and CGI-S and adverse effects (AE) were recorded in every visit. Results: SAS total scores decreased significantly during the study in patients with DIP (P<0.001), and mild AEs were detected. Treatments with pramipexole did not show an antiakathisia effect during the study, while 2 subjects experienced deterioration of akathisia and mood symptoms. The psychiatric symptoms of schizophrenia showed a trend of improvement during the study, but there was no improvement in depressive mood. Conclusion: A low dose of pramipexole can significantly relieve antipsychotic-induced parkinsonism, but not akathisia. Improvements in psychiatric symptoms of schizophrenia were found, but the results of this study need to be validated in a larger sample. No improvement of mood disorder was detected. Keywords: extrapyramidal symptoms, antipsychotics, pramipexole, clinical trial